2021
DOI: 10.1038/s41598-021-82206-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone self-administration activates the mitogen-activated protein kinase/ mitogen- and stress-activated protein kinase (MAPK-MSK) signaling pathway in the rat dorsal striatum

Abstract: To identify signaling pathways activated by oxycodone self-administration (SA), Sprague–Dawley rats self-administered oxycodone for 20 days using short—(ShA, 3 h) and long-access (LgA, 9 h) paradigms. Animals were euthanized 2 h after SA cessation and dorsal striata were used in post-mortem molecular analyses. LgA rats escalated their oxycodone intake and separated into lower (LgA-L) or higher (LgA-H) oxycodone takers. LgA-H rats showed increased striatal protein phosphorylation of ERK1/2 and MSK1/2. Histone H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 93 publications
2
2
0
Order By: Relevance
“…The effect is most pronounced in 11-12 hour daily access models (Nguyen et al, 2021;Nguyen et al, 2017), but it also appears to lesser extent in 8 h (Nguyen et al, 2020a;Nguyen et al, 2019) and even in 1 h (Nguyen et al, 2018) daily access paradigms. Similar patterns have been present in oxycodone IVSA data published by other groups (Blackwood et al, 2019a;Blackwood et al, 2021;de Guglielmo et al, 2020;Illenberger et al, 2023a;Illenberger et al, 2023b;Kallupi et al, 2020;Matzeu and Martin-Fardon, 2020), and while additional studies are insufficiently precise in methods for full clarity, inspection of the acquisition pattern for infusions suggests a similar increase in intake after a weekend abstinence interval (Fu et al, 2022;Kimbrough et al, 2020). Our model also showed that LgA oxycodone IVSA leads to increased brain reward thresholds across a week of sequential sessions of intracranial self-stimulation (ICSS), followed by a return towards baseline conditions after 60 h abstinence (Nguyen et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
“…The effect is most pronounced in 11-12 hour daily access models (Nguyen et al, 2021;Nguyen et al, 2017), but it also appears to lesser extent in 8 h (Nguyen et al, 2020a;Nguyen et al, 2019) and even in 1 h (Nguyen et al, 2018) daily access paradigms. Similar patterns have been present in oxycodone IVSA data published by other groups (Blackwood et al, 2019a;Blackwood et al, 2021;de Guglielmo et al, 2020;Illenberger et al, 2023a;Illenberger et al, 2023b;Kallupi et al, 2020;Matzeu and Martin-Fardon, 2020), and while additional studies are insufficiently precise in methods for full clarity, inspection of the acquisition pattern for infusions suggests a similar increase in intake after a weekend abstinence interval (Fu et al, 2022;Kimbrough et al, 2020). Our model also showed that LgA oxycodone IVSA leads to increased brain reward thresholds across a week of sequential sessions of intracranial self-stimulation (ICSS), followed by a return towards baseline conditions after 60 h abstinence (Nguyen et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
“…Consistent with this known biological function, the MAP kinase pathway was the most enriched GO molecular function term associated with the set of differentially expressed genes in opioid cases versus controls (P adj < 0.01) (Figure 1I) (Chen et al, 2013;Kuleshov et al, 2016) . Both the input transcription factors to the 388 loci (FOS AP1 factors) and output MAPK genes are consistent with known addiction pathways (Al-Hasani and Bruchas, 2011) (Blackwood et al, 2021) (Browne et al, 2020) (Qiao et al, 2021) (Brynildsen et al, 2020).…”
Section: Identification Of Homogeneous H3k27ac Hypoacetylation Eventssupporting
confidence: 62%
“…< 1×10 -7 ) (Figure 1B,C, Table S2). An exemplar locus linked to target gene DUAL-SPECIFICITY PHOSPHATASE 4 (DUSP4) in DLPFC promoter capture Hi-C data, involved in the addiction-relevant GPCR and MAPK signaling pathways (Blackwood et al, 2021;Qiao et al, 2021), is shown in Figure 1D. Strikingly, no significant hyperacetylated peaks in cases were found.…”
Section: Identification Of Homogeneous H3k27ac Hypoacetylation Eventsmentioning
confidence: 98%
“…One paper reported that an inhibitor of bromodomain and extra-terminal (BET) proteins, a class of histone acetylation readers, was unable to alter oxycodone-induced CPP in mice ( 81 ). In another study, using a model of intravenous self-administration, it was shown that oxycodone leads to an increase in histone H3 phosphorylation at serine 10 and acetylation at lysine 14 ( 82 ). Interestingly, this histone acetylation is mediated by CREB pathway, which is consistent with other studies that have shown that oxycodone activates CREB ( Table 3 ).…”
Section: Molecular Adaptations Following Chronic Treatmentsmentioning
confidence: 99%